The Influence of Leadership and Work Discipline Towards Employee Performance at PT. Kereta Api Indonesia (Persero) Divisi Regional I Sumatera Utara - Muhammad Fahmi; Fenny Sanika (AIBPM Publisher, 2019)
The purpose of this research is to find out the siginificant influence of leadership and work discipline against the employee performance in PT KeretaApi Indonesia, (Persero) Divisi Regional I Sumatera Utara. Research methods the research done is associative, where variables are measured by Likert scale. Method of data collection is done with the list of questions, interviews, documentation study and observation. . The population in this research is all of the employeeson the PT Kereta Api Indonesia Divisi Regional I Sumatera Utara totalling87 people.Data processing using the software SPSS version 20, with descriptive analysis and multiple regression analysis of hypothesistesting. The results showed that, partially, there are significant relationship between leadership and work discipline toward employee performance. And simultaneously, there are significant relationship between leadership and work discipline as the dependent variables and employee performance as independent variable.